A debate on the theory of contradictory class locations and middle classes: reproduction strategies of small traders in Turkey. (15th March 2023) - Altınoklu, Müge Neda; Boyraz, Cemil
ABSTRACT: The global economic crisis and the associated economic downturn in Turkey revitalized debates about the theory and politics of the middle classes. The significance of the middle classes has historically been shaped by not only the 'declining' boundaries of their objective class position but also their 'rising' importance in the reproduction of capital accumulation and hegemonic relations. Inspired by the notion of 'contradictory class locations' offered by Erik Olin Wright to make sense of the growing middle class of nonmanual labor in contemporary capitalist societies, and with a particular focus on Turkey's hardware sector and small traders in the Karaköy region, this article addresses the specific historical conditions of these small traders' class formation and analyzes their experiences with changing market conditions, their approaches to the functioning of market mechanisms, and the role of the state, as well as forms of their political representation.